DNA methylation profile at a satellite region is associated with aberrant placentation in cloned calves. (October 2018) - Silveira, Márcia Marques; Salgado Bayão, Henrique Xavier; dos Santos Mendonça, Anelise; Borges, Naiara Araújo; Vargas, Luna Nascimento; Caetano, Alexandre Rodrigues; Rumpf, Rodolfo; Franco, Maurício Machaim
Abstract: Introduction: Cloning via somatic cell nuclear transfer (SCNT) has been associated with a variety of pathologies, primarily in the placenta, and these alterations may be associated with aberrant epigenetic reprogramming of the donor cell genome. We tested the hypothesis that DNA methylation patterns are not appropriately established after nuclear transfer and that those altered patterns are associated with specific aberrant phenotypes. Methods: We compared global and specific placental DNA methylation patterns between aberrant and healthy SCNT-produced calves. Foetal cotyledon samples of ten SCNT pregnancies were collected. Global DNA methylation and hydroxymethylation levels were measured using an ELISA-based assay and specific DNA methylation of satellite I, and α-satellite repeat elements were measured using bisulfite PCR. Results: Our analysis revealed that the SCNT-produced calves, which showed aberrant phenotypes, exhibited a reduced methylation pattern of the satellite I region compared to that of healthy calves. In contrast, global methylation and hydroxymethylation analyses showed higher levels for both cytosine modifications in SCNT-produced female calves with aberrant phenotypes. The satellite I region showed most of the sequences to be hypermethylated in live cloned calves compared with those in deceased calves. Discussion: Our results suggest that this satellite I region could be used as an epigenetic biomarker for predicting offspring viability. Studies evaluating DNA methylation patterns of this satellite region in the donor cell genome or embryo biopsies could shed light on how to improve the efficiency of SCNT cloning. Highlights: Global methylation and hydroxymethylation are higher in placenta of aberrant clones. Cloned calves show less methylation in the satellite I DNA than control animals. Clones with aberrant phenotypes show less methylation in the satellite I DNA. Live cloned calves show hypermethylation in the satellite I compared to deceased ones.